Survival of captive-raised light-footed Ridgway’s rails is influenced by release date and time in wild - Kimberly A Sawyer; Courtney J. Conway (Avian Conservation and Ecology, 2025)
Captive breeding and translocation programs are an increasingly common conservation tool and management strategy used for some of the rarest and most endangered species in the world. These programs come at a high cost, and many translocation programs fail to monitor animals after release. Light-footed Ridgway’s rails ( Rallus obsoletus levipes ) are federally endangered marsh birds endemic to coastal wetlands of southern California and northern Mexico. Juvenile captive-raised light-footed Ridgway’s rails have been released into marshes within their U.S. range for >20 yr, but little effort has been devoted to post-release tracking of their movement and survival. We used satellite GPS transmitters to track survival of 46 juvenile captive-released and 42 juvenile wild-caught light-footed Ridgway’s rails from 2020–2022. Our results suggest that juvenile captive-released rails had lower initial daily survival probability (0.979) compared with that of juvenile wild-caught rails (0.994). Survival probability of captive-released rails increased with time in the wild, matching that of wild birds at about 100 d post-release. Survival of captive-released birds was most influenced by the date birds were released (releases in early summer had the highest survival). Our study emphasizes the importance of post-release monitoring as part of any captive breeding and translocation program and provides important insight into management strategies that may improve captive-released rail survival in the wild.